The Social Cost of Blockchain: Externalities, Allocation of Property Rights, and the Role of the Law - Edoardo D Martino; W. Georg Ringe (University of Hamburg, Institute of Law and Economics (ILE), 2024)
In the past decade, the legal and economic literature on blockchain technology and its applications has flourished. This new technology holds great promise for enhancing the efficiency of contracting. Building on the classic Coase theorem, blockchain as a decentralised mechanism of decision-making should be superior to centralised regulation, possibly yielding substantial efficiency gains. Notably, it also has the potential to improve the allocation of property rights and reduce transaction costs. However, many of these enthusiastic views about what blockchain technology may bring are overblown. This article demonstrates that blockchain creates a variety of new externalities, which cannot be addressed by the decentralised actors using it. The most obvious of them is the environmental externality stemming from the energy-intensive mining process. In addition, more immediate externalities emerge, for example through the operational and legal risks of being part of a blockchain transaction, which are particularly evident in the crypto economy. Moreover, issues surrounding blockchain governance may exacerbate these challenges. In conclusion, we propose several regulatory strategies to mitigate these shortcomings and harness the full potential of blockchain technology.
Keywords: K11; K22; K29; 330; blockchain technology; Coase theorem; social cost